2014
DOI: 10.1096/fj.14-251314
|View full text |Cite
|
Sign up to set email alerts
|

The thermosensitive TRPV3 channel contributes to rapid wound healing in oral epithelia

Abstract: The oral cavity provides an entrance to the alimentary tract to serve as a protective barrier against harmful environmental stimuli. The oral mucosa is susceptible to injury because of its location; nonetheless, it has faster wound healing than the skin and less scar formation. However, the molecular pathways regulating this wound healing are unclear. Here, we show that transient receptor potential vanilloid 3 (TRPV3), a thermosensitive Ca 2+ -permeable channel, is more highly expressed in murine oral epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 53 publications
(95 reference statements)
1
63
0
Order By: Relevance
“…Similarly, TRPV3 mRNA was found to be upregulated in keratinocytes derived from patients with hypertrophic post burn scars who also reported itching [114]. Moreover, mouse studies have linked TRPV3 to epithelial wound healing in skin and oral mucosa [105,115]. …”
Section: Contributions Of Trp Channels To Skin Biology and Pathophmentioning
confidence: 99%
“…Similarly, TRPV3 mRNA was found to be upregulated in keratinocytes derived from patients with hypertrophic post burn scars who also reported itching [114]. Moreover, mouse studies have linked TRPV3 to epithelial wound healing in skin and oral mucosa [105,115]. …”
Section: Contributions Of Trp Channels To Skin Biology and Pathophmentioning
confidence: 99%
“…Several lines of evidence suggest a critical involvement of TRPV3 in cutaneous sensations, hair development, and barrier function (Cheng et al, 2010;Aijima et al, 2015;Duchatelet and Hovnanian, 2015).…”
Section: Role Of Trpv3 In Skin Physiologymentioning
confidence: 99%
“…Further studies should be carried out to draw a strong conclusion from global analysis of fatty acids at the lesional site. It was previously reported that TRPV3 regulates skin barrier formation through epidermal growth factor signaling 33 and might play an important role in wound healing 34 .…”
Section: Discussionmentioning
confidence: 99%